Mistakes: prevent or prepare? - Meera Rada Krishnan, * (Sunway College Kuala Lumpur, 2015)
The heart of a dynamic and holistic learning culture is fuelled primarily by innovation in teaching, making learning a voyage of discovery for the learner and the educator. However, it is undeniable that in our current education environment, there is an increasing focus on quality control, performance indicators and competitiveness, resulting in innovation being stifled out of fear of making mistakes impacting performance and perception (Zimmermann, 2011). Learning in order to gain knowledge holds the key to understanding. Paradoxically, unlearning allows new learning to take hold and inadvertently broadens students’ application skills of prior knowledge (Lee, 2002). The objective of this study is to evaluate the impact of allowing students to learn constructively from their mistakes on enhancing students’ self- confidence and ultimately inspiring them to become more daring and critical thinkers. A study was conducted on 42 pre-university level students to assess their improvement in terms of response time and correct answers when given the opportunity to use common mistakes as a learning tool. Preliminary analysis of the results show almost 86% of students show considerable improvement in response time while 81% demonstrated better understanding of key concepts. This indicated that students who were allowed to prepare themselves using mistakes clearly were able to better apply their conceptual knowledge at a substantially faster rate, compared to those who were constrained by the fear of making mistakes